Possibilities for optimizing physical training for children through the pilot program: Judo in school from rural areas - Kunszabo, Mihai (Arena-Journal of Physical Activities, 2022)
Purpose. The main purpose of the research is to highlight the effects in terms of physical training of an experimental program applied to students aged 8-10, through the hours of physical education with selected content from judo. Methods. A number of 24 male subjects, students of Ghioroc Secondary School were tested. For the statistical interpretation of the research results we used in the comparison of the research groups (control and Experimental) the Independent Sample t Test, arithmetic mean, standard deviation and statistical significance through the statistical program IBM SPSS ver. 23, both at the level of the initial test and at the level of the final test. Results. From the statistical interpretation of the research results we can draw the following conclusions: at the beginning of the experiment the two research groups present average values without statistically significant differences (p> 0.05) at all test samples and at the end of the experiment, the two research groups show significant statistic differences in all test samples as follows: p <0.05 in test samples: long jump from the spot; respectively p <0.001 at the shuttle test, trunk lifts, push-ups and knee bends. Conclusions. The experimental hypothesis was confirmed, the results obtained supporting this. At the level of the initial test, the research groups presented similar values, the results of comparing the average values highlighting the lack of significant differences (p> 0.05) in all test samples. Based on the data collected at the end of the experiment, it was found that the total physical capacity of the subjects was significantly improved at the thresholds of statistical significance of p <0.05 and p <0.001, demonstrating the superiority of the application of judo sports content compared to classic content, for 1 school year, at the physical education classes of 8-10 year old students from rural areas.